Establishing self-concordant goals: a longitudinal study on the influence of ego identity on goal self-concordance - Cao, Lu; Ma, Jianhong (Frontiers in Psychology, 2024)
Self-concordant goals are those that align closely with an individual's intrinsic interests and values, driving autonomous motivation, and resulting in higher satisfaction and goal achievement. The relevance of studying the link between ego identity and goal self-concordance lies in understanding how a well-defined ego identity can foster the pursuit of authentic and fulfilling goals.This study investigates the relationship between ego identity and goal selfconcordance, focusing on how individuals' sense of identity influences their alignment with personal goals. METHODS: Data were gathered through a cross-sectional analysis of 292 students and a longitudinal follow-up with 98 participants over two intervals.Results confirmed significant correlations between ego identity status and various dimensions of goal self-concordance. Notably, different ego identity statuses exhibited distinct levels of goal self-concordance, ranked from highest to lowest as follows: identity achievement, achievement-foreclosure intermediate, moratorium, foreclosure, moratorium-diffusion intermediate, and diffusion. Cross-lagged analysis revealed a causal relationship where ego identity influences goal self-concordance, providing insights into the cognitive and behavioral processes involved in goal setting.DISCUSSION: This study extends the implications of the goal self-concordance model and reveals a causal relationship between ego identity status and goal self-concordance. From a practical perspective, our findings suggest that educational and developmental interventions aimed at supporting identity development and commitment could lead to more selfconcordant goal setting. Such programs could ultimately promote greater well-being and personal growth among students.